2017
DOI: 10.1016/j.physletb.2016.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter and inflation in R+ζR2 supergravity

Abstract: As is well known, the gravitational degrees of freedom contained in R + ζR 2 (super)gravity lead to Starobinsky's potential, in a one-field setting for inflationary Cosmology that appears favored by Planck data. In this letter we discuss another interesting aspect of this model, related to gravitino production, with emphasis on the corresponding mass spectrum. Assuming that supersymmetry is broken at a very high scale, Super Heavy Gravitino Dark Matter (SHGDM) and Starobinsky's inflation can be coherently unif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…[28,29], whereas the gravitino production sourced by inflation was considered in Refs. [30,31,32], though without specifying a particular model. In this paper we apply the methods of Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28,29], whereas the gravitino production sourced by inflation was considered in Refs. [30,31,32], though without specifying a particular model. In this paper we apply the methods of Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we apply the methods of Refs. [30,31,32] to the specific Starobinsky-Polonyi supergravity model proposed in Refs. [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the study of explicit interactions of the inflaton with low energy phenomenology has been rather poorly studied in the literature or to some extent fine-tuned through an extensive use of non minimal coupling to gravity or gauge corrections [30][31][32][33][34][35][36][37][38][39][40][41]. Attempts to incorporate inflation within a context of low scale supersymmetry breaking [44] has however shown that a complete description of low energy phenomenology of an inflation model can lead to rich constraints relating primordial cosmology to LHC physics.…”
Section: Jhep12(2017)072mentioning
confidence: 99%
“…f (R) theory has several successful applications in the domain of cosmology [46][47][48][49][50]. However, it should be associated with other tests to achieve the success of GR in the solar system [51].…”
Section: Introductionmentioning
confidence: 99%